If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24x+48-36=18x-36
We move all terms to the left:
24x+48-36-(18x-36)=0
We add all the numbers together, and all the variables
24x-(18x-36)+12=0
We get rid of parentheses
24x-18x+36+12=0
We add all the numbers together, and all the variables
6x+48=0
We move all terms containing x to the left, all other terms to the right
6x=-48
x=-48/6
x=-8
| 7p-4(p+4)+20=25 | | 4y-11-11+22=180 | | 1/2x+(x-15)+100+(x-25)+1/2x=540 | | 3/n=5/12 | | 30=d/6 | | 2x=3x+26 | | x+.48=3.5 | | 8.7=d/6 | | 6=2(y+2)y= | | 4y=5=21 | | 36n*36n=144 | | y=2(+2)y= | | 4.5y=16 | | -4m+2=-5m+9 | | 14p-1/5=1 | | 8v=4(4v+2) | | 0=96+80x-16x^2 | | 86+x=2x+10 | | 0=-16x^2+64x-80 | | 80=-16x^2×64x | | 16+2y=38 | | 4(15-2x)-4-(6-8x)=6x | | 6x+-6=12 | | 3s−4=2 | | 6k^2+11k+4=0 | | 6x+-6=12x | | 7x-4=115 | | 35x=8,75•10 | | 12n^2-52n+48=0 | | X-10=6x+3 | | 9/4y−12=4/1y−4 | | 2w=65-2w |